Matrix Hybridization Effects on Interlaminar Fracture Toughness of Glass Epoxy Laminates using Nano and Micro fillers (Fracture and Structural Integrity, 2023)
The composite materials are normally made of reinforcements and resins. High-performance composites are generally termed hybrid composite materials. Generally, fiber-reinforced composite laminates are very weak in their out-of-plane properties, to address this issue unidirectional (UD) Glass laminates are prepared by modifying epoxy matrix using plasma-treated multi-walled carbon nanotubes (MWCNTs) and compared with low-cost micro fillers like Aluminum oxide (Al2O3) and Sodium Carbonate (Na2CO3) in the epoxy matrix. All these Nano and Micro fillers were loaded in the range of 0.5wt% to 2wt% in epoxy. The addition of these fillers in the epoxy matrix was found to be effective in increasing the out-of-plane load-bearing capacity of the composites as compared to plain Glass epoxy laminates. Also, the fracture toughness enhanced in the range of 20-26% and 14-17.5% under mode I and mode II loading respectively. Scanning electron microscopic analysis was done for delaminated glass laminates and found that the delamination of fibers is the significant failure mechanism during crack initiation from the crack tip.
Keywords: Fracture Toughness; Delamination; Hybrid matrix; MWCNTs; Laminate